Log in to add a comment

## Answers

--------------- ---------------- ----

(x - 1)(x - 2) (x - 2)(x - 3) 3

1 [ 1 + 1 ] = 2

**-------------[Taken 1 / (x - 2) Common ]**

------- --------- --------- ----

(x - 2) (x - 1) (x - 3) 3

1 [x - 3 + x - 1] = 2

------- ------------------ ----

(x - 2) (x - 1)(x - 3) 3

1 [ 2x - 4 ] = 2

------- ------------- ----

(x - 2) x² - 4x + 3 3

2x - 4 = 2

---------------------------- -----

x³ - 4x² - 2x² + 3x - 6 3

2x - 4 = 2

---------------------- -----

x³ - 6x² + 3x - 6 3

(2x - 4)3 = 2(x³ - 6x² + 3x - 6)

6x -12 = 2x³ -12x² +6x -12

**--[6x - 12 gets cancelled on both the sides]**

2x³ - 12x² = 0

2x²( x - 6 ) = 0

**2x² = 0 OR x - 6 = 0**

**x = 0 OR x = 6**

**Sincerly Hope Answer is Correct**

**If Then,**

**Hope U Understood**

**Mark This Brainliest If This Helped You**

**Thankx**